Traits of patients seen via telemedicine versus in person for new-patient visits in a fertility practice - Vinita M. Alexander, M.D., M.S; Allison P. Schelble, M.D; Kenan R. Omurtag, M.D (Elsevier, 2021)
Objective: To assess the differences in demographics, the likelihood of receiving treatment, and the clinical outcomes between new patients seen via telemedicine and those seen in person in an academic fertility practice. Design: Retrospective cohort study. Setting: University-based fertility clinic. Patient(s): All new patients seen via telemedicine between June 1, 2017, and February 29, 2020, were compared with an equal number of all new patients seen in person between May 1, 2019, and June 30, 2019. Intervention(s): None. Main Outcome Measure(s): The primary outcome was receiving treatment after a new-patient visit. Binary logistic regression analyses were performed to estimate the odds ratio for not receiving treatment according to distance to the clinic and duration of infertility. The secondary outcomes included treatment recommendation, time to treatment initiation, and time to positive pregnancy test (if achieved). In addition we assessed patient demographics and visit traits per patient encounter. Result(s): The telemedicine and in-person groups each contained 70 patients. The following were similar between the groups: age, body mass index, Area Deprivation Index, diagnosis made at the new-patient visit, and the number of clinic contacts before starting treatment. Compared with patients who had in-person new-patient visits, those who had telemedicine new-patient visits lived farther from the clinic (mean, 223.6 vs. 69.28 miles) and had a longer duration of infertility (mean, 41.9 vs. 19.49 months). No differences were noted between the groups in the following outcomes: percent that received treatment, time to treatment initiation, or time to pregnancy. Telemedicine new-patient visits were shorter than in-person new-patient visits (mean, 56.3 ± 9.1 vs. 59.3 ± 4.6 minutes) and less likely to contain documentation of height or weight. Conclusion(s): Telemedicine appears to be of particular interest to patients who live farther from clinics and have longer durations of infertility, and it could reduce visit times. New patients seen in person and those seen via telemedicine are equally likely to pursue treatment. Telemedicine consultation for new-patient visits is feasible in an academic fertility practice and may be especially useful during a pandemic and in non-pandemic times in areas with limited access to fertility specialists.